The relationship between childhood adversity and violence to others among individuals with psychosis: a review and meta-analysis - Green, Kathleen; Browne, Kevin; Chou, Shihning (SAGE Publications, 2017)
Background: There is a growing body of literature identifying a relationship between experiences of child abuse and symptoms of psychosis in adults. However, the impact of this relationship on risk of violence has not been systematically explored. Aims: This meta-analysis aimed to consider the influence of childhood abuse on the risk of violence amongst individuals with psychosis. Method: Five bibliographic databases and two grey literature resources were systematically searched to identify quantitative research which measured risk of violence and experiences of childhood maltreatment in individuals with psychosis. Risk of bias for each study was assessed under pre-defined criteria. Logged odds ratios were synthesised quantitatively in a meta-analysis. Results: A total of 6298 studies were identified, 11 of which were included in the final analysis (N = 2215), all studies were of a cross-sectional or case-control design. Individuals with psychotic illnesses who reported historical child maltreatment were at approximately twice the risk of perpetrating violence than patients who reported no early abuse (OR = 2.46 (95% CI = 1.91 – 3.16). There was no statistical heterogeneity between main effects (τ = 0.00; Χ² = 8.87, df = 10, p = 0.54, I² = 0%). Discussion: Risk assessments and interventions may benefit from considering the unique contribution of trauma to violence in this population. Future research considering the interaction between childhood experiences and other risk factors for violence in this population, including specific symptoms of psychosis, would inform the current findings. Findings are limited by the lack of longitudinal research in this area, and there was some evidence of publication bias.